Quality Analysis of Probiotic Animal Food Products: A Test of Protein and Blood Fats - Widia Widia; Faizah Alivia Putri; Tutinah Tutinah; Robby Gus Mahardika (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2022)
Dissemination on Bangka Island will be carried out at the UBB Probio_FM Technology Product Downstream Partnership activity for the Institutionalization of Community Enterprises based on Organic Agriculture.The dissemination program on Bangka Island is aimed at increasing the number of technology users on Bangka Island. Animal food products are one of the agricultural commodities that have high economic value, especially on Bangka Belitung Island. Animal food products are a source of protein, examples of animal food products include fish, chicken and duck meat, eggs, and beef. Catfish, tilapia, duck and broiler and laying duck farming businesses will be carried out in the MF activities of the 2022 design shop, with the aim of producing healthy food products. The results of farming activities such as fresh catfish, tilapia, eggs, chicken meat and ducks, will be used as further research samples to analyze the content of protein, fat and cholesterol. The purpose of this study is to analyze the content of cholesterol, protein, and blood fats in duck eggs, chicken and duck meat, and probiotic fish. Produce probiotic food products with labels containing cholesterol, protein, and fat values. The timing of the implementation of this research began in October and ended in December 2022. The research was conducted at the FPPB UBB Basic Laboratory. The form of research is laboratory research, using a random design method using several samples as a comparison of treatments, preparing samples, testing cholesterol and fat protein content, collecting data and analyzing data. The protein content obtained was duck 31.34%, duck eggs 1.229%, probiotic catfish 42.37%, and non-probiotic catfish 34.8%. The fat content obtained was duck meat 33.79%, duck eggs 46.21%, probiotic catfish 21.46%, and non-probiotic catfish 21.359%. Keywords: Animal Food Products, Probio FM Technology, Protein Content, Fat Content.